Topoisomerase II-α expression increases with increasing Gleason score and with hormone insensitivity in prostate carcinoma. Issue 7 (23rd March 2006) - Hughes, C; Murphy, A; Martin, C; Fox, E; Ring, M; Sheils, O; Loftus, B; O'Leary, J
Abstract : Aim: To investigate and compare topoisomerase II-α expression in benign prostatic hyperplasia (BPH), prostate cancer of varying Gleason scores and hormone-insensitive prostate cancer. Methods: The immunohistochemical expression of topoisomerase II-α antibody in the above-mentioned diagnostic categories was investigated and compared. Results: Increased expression of topoisomerase II-α was seen in the prostate cancers of Gleason scores 7 and 8–10 (p = 0.000) compared with prostate cancers of Gleason score 6 and BPH (p = 0.245). Statistically significant differences were found in the topoisomerase II-α gene expression between prostate cancers categorised by Gleason Score. Also, increased expression of topoisomerase II-α was seen in the known hormone-resistant prostate carcinomas compared with prostate cancers with no hormone treatment in the subgroup with Gleason scores 8–10, which approached statistical significance (p = 0.081). No statistically significant difference was observed in topoisomerase II-α expression between the groups with BPH and prostate carcinoma of Gleason score 6 (p = 0.245). Conclusion: Topoisomerase II-α expression was found to increase with the known prognostic marker Gleason score and with hormone insensitivity. Objective evidence is provided for clinical trials with drugs targeting topoisomerase II-α to be targeted to patients with prostate cancers of Gleason Score >6 and, in particular, prostate cancers of Gleason Scores 8–10.